Transparency of informed consent in pilot and feasibility studies is inadequate: a single-center quality assurance study - Khan, MIU; Mbuagbaw, L; Holek, M; Bdair, F; Durrani, ZH; Mellor, K; Eddy, S; Eldridge, SM; Chan, CL; Campbell, MJ; Bond, CM; Hopewell, S; et al. (BioMed Central, 2021)
Background Pilot and feasibility studies (PAFS) often have complex objectives aimed at assessing feasibility of conducting a larger study. These may not be clear to participants in pilot studies.